Conduction system pacing is superior to biventricular pacing in patients with heart failure: Insights from the pooled clinical studies - Zhang, Jie; Li, Feng; Zhang, Zhi-Yuan; Yang, Fan; Kong, Qi; Chen, Jia-Yi; Zhang, Lei; Liu, Huan-Huan; Chen, Xu-Fei; Ye, Yu-Heng; Wang, Ru-Xing (Frontiers in Physiology, 2023)
Background: The effects of conduction system pacing (CSP) compared with conventional biventricular pacing (BVP) on heart function in patients with heart failure remain elusive. Methods: PubMed, Embase, Cochrane's Library and Web of science databases were searched up to 1 October 2022 for pertinent controlled studies. Random or fixed-effect model were used to synthesize the clinical outcomes. Subgroup analysis was performed to screen the potential confounding factors. Results: Fifteen studies including 1347 patients were enrolled. Compared with BVP, CSP was significantly associated with shortened QRS duration [WMD -22.51ms; P = 0.000], improved left ventricular ejection fraction [WMD 5.53%; P = 0.000], improved NYHA grade [WMD -0.42; P = 0.000] , higher response rate and lower heart failure rehospitalization rate. CSP resulted in better clinical outcomes in higher male proportion group than lower one compared with BVP. No significant differences of clinical outcomes were observed between left bundle branch area pacing (LBBaP) and his bundle pacing (HBP) except the pacing threshold. The pacing threshold of LBBaP was significantly lower than those in BVP and HBP. Conclusions: This study suggests that CSP is superior to conventional BVP for HF patients. In a higher male proportion group, CSP might be associated with more benefits than BVP.